An Economics of Moth bean Processing in Nagaur District of Rajasthan - Kumawat, Subhita (Annals of Arid Zone, 2016)
The present study was devoted to an economics of moth bean processing in Nagaur district of Rajasthan. The processing cost and returns analysis revealed that moth bean is processed into different products such as parched moth bean, parched moth bean dal, moth bean flour (besan), milled moth bean for human beings and livestock etc. The processor purchased moth bean at the rate of Rs. 5700 q-1 and sold moth bean dal at a price of Rs. 7600 q-1. Broken moth bean dal which is generally used for besan making was sold @ Rs. 5000 q-1 and churi which is used as livestock feed was sold @ Rs. 1600 q-1. The total cost incurred by the processor was Rs. 6058.08 and returns after processing of moth bean were Rs. 6544.00. Net returns per quintal of processed moth bean were Rs. 485.92. The processors, on an average, earned a profit of 8.52% on the purchase price of moth bean. The mark-up (per cent increase) in moth bean price after processing was 33.33%. The policy implication based on the findings of the present study pulse processing is beneficial to both producers, the public and govt. in general. For farmers, processing facilities create strong markets. Farmers/processors have a natural incentive to aggressively pursue commodity supplies to keep their plants fully utilized. This will result in farmers receiving higher prices than they would get otherwise. The processing facilities create jobs, generate tax revenues, and increase economic activity to benefit many local businesses.